1993
DOI: 10.1042/bj2960639
|View full text |Cite
|
Sign up to set email alerts
|

Structure and contribution to the heparin cofactor II-mediated inhibition of thrombin of naturally oversulphated sequences of dermatan sulphate

Abstract: Dermatan sulphate (DS) obtained from bovine and pig mucosa and pig skin, and charge-enriched fractions of a selected DS preparation, were characterized in terms of charge density, M(r) and disaccharide composition of chondroitin ABC lyase digests, and by 13C-n.m.r. spectroscopy. Besides the major IdoA-GalNAc4SO3 sequences, all DS preparations contain about 10% disulphated disaccharide sequences (mostly IdoA2SO3-GalNAc4SO3, with minor amounts of IdoA-GalNAc4,6SO3). DS fragments (prepared by radical-catalysed de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…(22). Only in the specific case of heparin cofactor II has a comparable high affinity interaction with DS been demonstrated, and this is dependent upon the presence of a specific, highly sulfated DS oligosaccharide sequence (23,24).In the present study, we demonstrate that HGF/SF also binds to DS with high affinity. This gives further insight into the specific structural requirements for oligosaccharide binding to HGF/SF.…”
supporting
confidence: 51%
“…(22). Only in the specific case of heparin cofactor II has a comparable high affinity interaction with DS been demonstrated, and this is dependent upon the presence of a specific, highly sulfated DS oligosaccharide sequence (23,24).In the present study, we demonstrate that HGF/SF also binds to DS with high affinity. This gives further insight into the specific structural requirements for oligosaccharide binding to HGF/SF.…”
supporting
confidence: 51%
“…Several reports have shown that heparan sulfate is necessary for the function of heparin-binding ligands, such as members of the fibroblast growth factor (FGF) family (9,10). Dermatan sulfate (DS) GAGs have also been found to bind heparin-binding growth factors, including FGF-2 (4), hepatocyte growth factor/scatter factor (11), heparin cofactor-II (12,13), platelet factor-4 (14), fibronectin (15), and protein C inhibitor (16). In human wounds, DS contributes the majority of FGF-2-dependent cell responsiveness, with heparan sulfate having lesser activity (4).…”
Section: Introductionmentioning
confidence: 99%
“…Wound fluid-derived DS, as well as physiologic concentrations of commercially purified DS, has been shown to promote FGF-2 function (1). DS and DS proteoglycans also bind to and influence the activity of other heparin-and HS-binding proteins including hepatocyte growth factor/scatter factor (2), thrombin (3), heparin cofactor II (4,5), fibronectin (6), platelet factor-4 (7), regulated on activation normal T cell expressed and secreted (RANTES) (8), and interferon-␥ (9, 10). Thus, although less well understood, DS-protein interactions are likely to be important events in control of several cellular behaviors.…”
mentioning
confidence: 99%